Sudut Pandang Tokoh Utama Terhadap Buku dalam Novel Fahrenheit 451 Karya Ray Bradbury - Sayu Asmarita; Fenty Sukmawaty; Saprudin (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2024)
Fahrenheit 451 is a novel that was written by American author, Ray Bradbury. This novel tells about book burning. As all we know, in a reality book has a great role for our life, because it contains of knowledge, information, experience and other useful thing. Meanwhile, in Fahrenheit 451 books must be burned. This phenomenon raises a question ‘why does the books must be burned?’. This study will describe point of view of the characters about book in Fahrenheit 451 according to Nurgiyantoro (2013). This study uses qualitative descriptive method. Objective approach is used in this study to understand the point of view of the characters because, it focuses on intrinsic elements analysis. The result of this study describes the five main characters’s point of view on ‘book’ in Fahrenheit 451.